2004
DOI: 10.1210/en.2003-1141
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead L2 Is Expressed in the Ovary and Represses the Promoter Activity of the Steroidogenic Acute Regulatory Gene

Abstract: Premature ovarian failure in a subgroup of women with blepharophimosis-ptosis-epicanthus inversus type 1 syndrome has been associated with nonsense mutations in the gene encoding a Forkhead transcription factor, Forkhead L2 (FOXL2). However, the exact function of FOXL2 in the ovary is unclear. We investigated the expression of FOXL2 in the mouse ovary during follicular development and maturation by RT-PCR and in situ hybridization. The FOXL2 mRNA is expressed in ovaries throughout development and adulthood and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
160
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 77 publications
10
160
0
4
Order By: Relevance
“…Knockout mice present a blockage in ovarian development secondary to failure in granulosa cell differentiation. 14,15 It has been recently reported that wild-type FOXL2 and its mutant may have differential regulatory activities of the apoptosis. According to Kim et al,17 FOXL2 mutant induces a lower number of apoptotic cells due to deregulation of the caspase activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout mice present a blockage in ovarian development secondary to failure in granulosa cell differentiation. 14,15 It has been recently reported that wild-type FOXL2 and its mutant may have differential regulatory activities of the apoptosis. According to Kim et al,17 FOXL2 mutant induces a lower number of apoptotic cells due to deregulation of the caspase activation.…”
Section: Discussionmentioning
confidence: 99%
“…12 FOXL2 overexpression induces apoptosis in ovarian granulosa cells, whereas its alteration induces premature ovarian failure due to the abnormal granulosa cell differentiation. [13][14][15] The missense point mutation (C402G) induces an amino-acid change in FOXL2 (C134W) but neither altered function nor mislocalization of the protein have been reported. 10 Previous studies have shown that this mutation is specific for the adult type granulosa cell tumors and is present in up to 95-97% of these tumors.…”
mentioning
confidence: 99%
“…We found that PPARGC1A and NR5A2, both involved in cholesterol homoeostasis (35), are stimulated by FOXL2. Previous works (13) have shown that FOXL2 represses expression of Star, a protein that controls cholesterol transport from the outer to the inner mitochondrial membranes. In agreement with this finding, FOXL2 up-regulated the cholesterol 25-hydroxylase whose product is a potent inhibitor of sterol synthesis (42).…”
Section: Analysis Of the Promoters Responding To Foxl2 In Terms Of Trmentioning
confidence: 98%
“…Only three of them, namely the genes encoding the gonadotropin-releasing hormone receptor (GnRHr), the alpha subunit of the gonadotropins (Cga), and the steroidogenic acute regulatory protein (StAR) have been reported so far (11)(12)(13). We have recently suggested that the aromatase gene (CYP19A1) is transcriptionally activated by FOXL2 (14,15).…”
mentioning
confidence: 99%
“…Mutations in FOXL2 cause blepharophimosis, ptosis, epicanthus inversus syndrome (OMIM #110100), and blepharophimosis, ptosis, epicanthus inversus syndrome type I is accompanied by premature ovarian failure of the affected female (Crisponi et al, 2001). FOXL2 is mainly expressed in undifferentiated granulosa cells, and blockage of ovarian follicle development because of the failure of granulosa cell differentiation was observed in FoxL2 lacZ homozygous mutant mice (Pisarska et al, 2004;Uda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%